Non-monotonic potential description of the cross-section, vector and tensor analyzing powers of the 6Li+12C elastic scattering at 30 and 50 MeV†. Issue 1 (January 2021) - Nilima, Athoy; Hossain, S; Azad, M M B; Billah, M M; Tariq, A S B; Uddin, M A; Bhattacharjee, S; Azizur Rahman, M; Basak, A K
Abstract: This work illustrates, for the first time, the analysis of tensor analyzing powers ( T 20, T 21, T 22 ) along with the differential cross-section (CS) and the vector analyzing power iT 11 for the 6 Li+ 12 C elastic scattering at 30 and 50 MeVwithin the framework of an optical model (OM) using microscopic shallow non-monotonic (NM) potentials. The NM potential is generated from the energy density functional formalism (EDF) [Brueckner et al., Phys. Rev., 168 (1968) 1184] using a realistic two-nucleon interaction incorporating Pauli Exclusion principle. The shallow NM potential can describe the experimental angular distributions of CS and analyzing powers of the elastic scattering data. The OM analysis of the data at this energy does not indicate their sensitivity on the nuclear matter incompressibility K .